Aesthetic Essentiality /Art. Poetry. Nature. Approaches) (XXI Century. Spanish Literature and Culture, 2013)
In this study, José Luis Puerto, approaches art, poetry and nature through  his notion of aesthetic essentialism, which is in constant renewal, linked at the same time to the renewal of the human and the world. Therefore, Puerto is correct when he says at the beginning of this essay: “Less is more, at the beginning of the twenty-first century”.
Keywords: essentialism; aesthetic; renewal; space